2022
DOI: 10.18632/aging.203970
|View full text |Cite
|
Sign up to set email alerts
|

The association between rs1260326 with the risk of NAFLD and the mediation effect of triglyceride on NAFLD in the elderly Chinese Han population

Abstract: Background: Accumulated studies have pointed out the striking association between variants in or near APOC3 , GCKR , PNPLA3 , and nonalcoholic fatty liver disease (NAFLD) at various ages from multiple ethnic groups. This association remained unclear in the Chinese Han elderly population, and whether this relationship correlated to any clinical parameters was also unclear. Objectives: This study aims to decipher the complex relevanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Hernaez et al 33 showed a correlation between patients with simple steatosis with higher ALT and rs780094-T. Tan et al 34 demonstrated that NAFLD patients with rs1260326 and rs780094 allele T were prone to progress to NASH with significant fibrosis, which would be developed from lean NAFLD 4 . In addition, Yuan et al 16 explored the mediation effect of TG on the association between rs1260326-T in GCKR and the risk of NAFLD in the elderly Chinese Han population. Yet, in our study, the association between rs1260326-C and the odds of lean NAFLD was mediated by waist circumference.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hernaez et al 33 showed a correlation between patients with simple steatosis with higher ALT and rs780094-T. Tan et al 34 demonstrated that NAFLD patients with rs1260326 and rs780094 allele T were prone to progress to NASH with significant fibrosis, which would be developed from lean NAFLD 4 . In addition, Yuan et al 16 explored the mediation effect of TG on the association between rs1260326-T in GCKR and the risk of NAFLD in the elderly Chinese Han population. Yet, in our study, the association between rs1260326-C and the odds of lean NAFLD was mediated by waist circumference.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence indicated that genetic variants have contributed to the occurrence and development of NAFLD 10,11 . Genome-wide association studies (GWASs) have shown several single nucleotide polymorphisms (SNPs), e.g., rs738409-G in patatin-like phospholipase domain containing 3 (PNPLA3) 11 , rs58542926-T in transmembrane 6 superfamily member 2 (TM6SF2) 12 , rs13107325-T in solute carrier family 39 member 8 (SLC39A8) 13 , rs6834314-A in hydroxysteroid 17-beta dehydrogenase 13 (HSD17B13) 14 and rs1260326-T in glucokinase regulator (GCKR) 15,16 associated with NAFLD-related comorbidities. Amongst the SNPs identified in GCKR, e.g., rs780093 and rs780094 were also identified as potential risk loci in metabolic syndrome 17 .…”
mentioning
confidence: 99%
“…The GCKR rs1260326-T is associated with metabolism-related mechanisms, such as glycolysis, fatty acid circulation, and saturation. Yuan et al observed an increase in TG levels of rs1260326-T carriers and demonstrated an association between GCKR rs1260326-T and fatty liver by studying the elderly Chinese Han population [ 72 ]. Furthermore, Nahass et al confirmed that GCKR rs1260326 allele T was associated with susceptibility to NAFLD [ 83 ].…”
Section: Metabolic-related Genes Influencing Nafldmentioning
confidence: 99%
“…GCKR P446L is a functionally deficient variant that increases fat production by inducing glycolysis ( Carlsson et al, 2020 ). The variation of GCKR is associated with a variety of lipid metabolism disorders ( Fernandes Silva et al, 2019 ), significantly affected the MAFLD ( Yuan et al, 2022 ). A meta-analysis showed that both the GCKR rs780094 and rs1260326 polymorphisms were significantly associated with an increased risk of MAFLD ( Li et al, 2021 ).…”
Section: Major Genetic Predisposition In Mafldmentioning
confidence: 99%